Mechanisms of Direction and Interpretation in Grammar (Journal of Hama University, 2019)
Direction is “to make the speech directed with a face and a clue”. This research has examined the methods of grammarians in directing the issues that have emerged from the seriousness of grammar and grammatical principles to return them in such a way as to gain the approval of these rules and assets. This, in turn, achieves the consistency of grammatical rules by demonstrating the effectiveness of grammatical directive Methods and structures contrary to the rules of grammar, and discusses the reasons of interpretation and its various mechanisms aimed at putting cohesion on the relationship between texts and rules to bring the phenomena of language contradicting the rules to the molds of these rules. In addition, the grammarians did not ignore the aspect of meaning in raising the rules, but rather made them a reference based on in directing the expression and weighing of the face of the object to another, and employed it in analyzing grammatical phenomenon; they realized that is not sufficient to explain the grammatical phenomenon, as the interest and completeness of the meaning and its exposition are the ultimate goal of the research in the grammatical lesson. The forefront of these mechanisms is: Response to the origin of the rule: either by deleting and appreciating or by getting an outcome through meaning and inclusion.The research concludes that the purpose of direction and interpretation is rooting out the grammatical base according to the different methods and means followed by each. It stresses on the importance of overcoming the apparent relations and looking at the hidden meanings behind them as well as the grammatical factors that confirm the view of the grammarians as cohesion between the grammatical industry and the meaning, in response to those who disagrees with that.